Social Enterprise Development Strategy through Ecobrick Production and Creative Marketing Campaigns: A Study of Srikandi Waste Bank - Larasati Siswanta, Anggitariani Rayi; Hidayah, Asmi Ayuning; Dewi, Isti Riana; Safitri, Telma Anis (Pena Dimas: Jurnal Pengabdian Masyarakat, 2025)
The Srikandi Waste Bank in Petir Village, Kalibagor, has faced challenges in managing waste due to limited human resources, insufficient managerial skills to apply science and technology, and inadequate infrastructure. As a result, unprocessed waste accumulates, occupying space and disrupting operations. To address this issue, community service activities were implemented, including training in the production of ecobricks and other marketable recycled products, the introduction of simple waste management technologies, and the optimization of storage spaces. These activities were complemented by post-training support, particularly in the use of social media for online marketing. The methodology adopted was the Asset-Based Community Development (ABCD) model, which emphasizes leveraging existing community resources and capacities. This approach enabled participants to apply newly acquired skills in creating added value from waste materials. The outcomes demonstrated increased production of ecobricks and creative recycled products, improved use of social media for marketing, and better organization of operational spaces. The synergy of this program has strengthened local waste management systems, contributed to environmental protection, and enhanced economic opportunities for the community. This aligns directly with several Sustainable Development Goals (SDGs): SDG 8 (Decent Work and Economic Growth) through the creation of green entrepreneurship opportunities; SDG 11 (Sustainable Cities and Communities) by fostering environmentally responsible waste practices; and SDG 12 (Responsible Consumption and Production) through the promotion of recycling and waste reduction. The program’s outcomes illustrate how community empowerment and the adoption of simple, replicable technologies can effectively support sustainable rural development and contribute to achieving global sustainability targets.